Chants d’oiseaux, cris de cochons et bruits des petites bestioles : les sons de la divination chez les Alangan de Mindoro (Philippines) - Laugrand, Frédéric B.; Laugrand, Antoine; Tremblay, Guy (Anthropologica, 2018)
Among the Alangan of Mindoro (Philippines), birds (with the exception of chickens) and smaller fauna are neither hunted nor eaten. Instead, these animals occupy a singular place in divinatory knowledge and cosmology, even in the context of recent Christianisation. Birds and insects manifest themselves mainly by the sounds they produce and they make themselves visible to humans when dangers arise. They play the role of augurs to the people around them. In this first initial study, the authors argue that sounds create meaningful links to the rituals of the haruspex, ornithomancy and entomancy. In the perspective of comparing different indigenous traditions in the Philippines, the authors hope to further develop a sonorous ethno-entomology.